2006
DOI: 10.1007/s10658-006-9080-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of seedling infection in epiphytotics of ascochyta blight on chickpea

Abstract: Didymella rabiei, the causal agent of ascochyta blight, survives on infected seeds and seedlings. Diseased seedlings originating from infected seeds occasionally serve as the source for primary infection in chickpea crops. Experiments carried out independently in Australia and in Israel provided quantitative information on the temporal and spatial distribution of ascochyta blight from initial infections and on the relationship between the amount of initial infection and the intensity of subsequent epiphytotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…Seed to seedling transmission Seed transmission rates for A. rabiei have been reported as 5% in field conditions (Kimber et al 2007) to 20-30% in glasshouse conditions Maden 1983). The production of diseasefree seed is seen as an important strategy in Pakistan, in areas free from A. rabiei infection (Mitsueda et al 1997).…”
Section: Diseased Seedmentioning
confidence: 99%
See 2 more Smart Citations
“…Seed to seedling transmission Seed transmission rates for A. rabiei have been reported as 5% in field conditions (Kimber et al 2007) to 20-30% in glasshouse conditions Maden 1983). The production of diseasefree seed is seen as an important strategy in Pakistan, in areas free from A. rabiei infection (Mitsueda et al 1997).…”
Section: Diseased Seedmentioning
confidence: 99%
“…The production of diseasefree seed is seen as an important strategy in Pakistan, in areas free from A. rabiei infection (Mitsueda et al 1997). The use of disease-free seed is crucial for susceptible chickpea cultivars as seedling foci rapidly develop into epidemics in conditions conducive to disease development (Kimber et al 2007). The rapid spread of ascochyta blight from primary infections in susceptible chickpea cultivars led to the development of a more rigorous PCR-based seed test in Australia.…”
Section: Diseased Seedmentioning
confidence: 99%
See 1 more Smart Citation
“…Infected seed may have reduced germination while seed to seedling transmission rates of up to 15% were recorded in field studies (Kimber et al 2006a). Infection on less than 1% of seedlings can lead to serious epidemics (Kimber et al 2007b). An overseas report (Kaiser and Hannan 1988) indicated that thiabendazole was amongst the most effective fungicides tested against seed-borne A. rabiei but Kimber and Ramsey (2001) found that a seed dressing of thiram plus thiabendazole (P-Pickel T®) was superior to thiram.…”
Section: Chickpea Pathologymentioning
confidence: 99%
“…The regular seasonal occurrences of Ascochyta blight epidemics suggest that the fungus has efficient mechanisms for overwintering from one season to the next. The main sources of primary inoculum are infected seeds that cause seedling infection [12,13] and air-borne ascospores produced in pseudothecia formed on chickpea infected debris [14,15]. During the growing season, secondary spread of the disease is driven by splash-borne pycnidiospores (conidia) produced in pycnidia that develop on Ascochyta lesions [11].…”
Section: Introductionmentioning
confidence: 99%